2019
DOI: 10.3390/ijms20082046
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Rescues Gene Pathways Involved in Vascular Expansion and Promotes Functional Angiogenesis in Subcutaneous White Adipose Tissue

Abstract: Exercise mitigates chronic diseases such as diabetes, cardiovascular diseases, and obesity; however, the molecular mechanisms governing protection from these diseases are not completely understood. Here we demonstrate that exercise rescues metabolically compromised high fat diet (HFD) fed mice, and reprograms subcutaneous white adipose tissue (scWAT). Using transcriptomic profiling, scWAT was analyzed for HFD gene expression changes that were rescued by exercise. Gene networks involved in vascularization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In retinoic acid treatment, activation of the brown fat-associated program in white adipocytes was mediated by vascular endothelial growth factor-stimulated angiogenesis (Wang et al, 2017). With exercise, vascularization in subcutaneous WAT is increased and may mediate an improved metabolic response (Min et al, 2019). EPO exhibits angiogenic and neovascularization activity in animal models (Yasuda et al, 1998;Ribatti et al, 1999;Kertesz et al, 2004;Wang et al, 2004;Li et al, 2007).…”
Section: Epo Protection In Mouse Adipose Tissue Inflammationmentioning
confidence: 99%
“…In retinoic acid treatment, activation of the brown fat-associated program in white adipocytes was mediated by vascular endothelial growth factor-stimulated angiogenesis (Wang et al, 2017). With exercise, vascularization in subcutaneous WAT is increased and may mediate an improved metabolic response (Min et al, 2019). EPO exhibits angiogenic and neovascularization activity in animal models (Yasuda et al, 1998;Ribatti et al, 1999;Kertesz et al, 2004;Wang et al, 2004;Li et al, 2007).…”
Section: Epo Protection In Mouse Adipose Tissue Inflammationmentioning
confidence: 99%
“…Epidemiological studies and clinical trials showed that fatty acids are associated with cardiovascular diseases [ 1 , 2 , 3 , 4 , 5 ], neurological diseases [ 6 , 7 , 8 , 9 ], non-alcoholic fatty liver disease [ 10 , 11 , 12 , 13 ], allergic diseases [ 14 , 15 , 16 ], and so on. Evidence from metabolomics experiments indicates that they participate in the metabolic pathways of related diseases [ 8 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, the free FA profile was found to be altered in both leukemia and pre-leukemic diseases, particularly C14:0, C16:0, and C18:0 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, chronic exercise training has been shown to attenuate adipocyte apoptosis (assessed via chromatin condensation) in inguinal AT, whereas apoptosis is increased by exercise in retroperitoneal AT. This is intriguing, given that markers of vascular expansion and capillary density in AT are reportedly increased by exercise training in rodents (56‐58) and humans (59), which is typically inversely associated with cell death. However, a prior study found that targeted deletion of mature adipocytes through apoptosis was not accompanied by aberrant inflammation in AT but rather increased the abundance of alternatively activated macrophages (60).…”
Section: Exercise and At Remodeling In Obesitymentioning
confidence: 99%